The Use of Android Based M-Learning toward Understanding Concept on Motion System Subject - Alimiah, Umi Syahadah; Mariana, Aditya; Linuwih, Suharto (Journal of Innovative Science Education, 2022)
Education on 4.1 era are much using the technological advances on Information and communication field. Internet technology is one of technology that allows everyone to do everywhere and anywhere learning or can be called as mobile learning. Learning by using mobile learning can support the development of education. At this time, students are required not only to produce high scores but also to understand the subject matter that has been taught, so that, it can be implemented in solving problems for everyday life. On the other hand, Students are required to be able to solve a problem with toughness. Therefore, students must have a theoretical foundation or concept that is in line with the facts and to create mature decisions. In sum to make the students to become people who always want to learn and learn.The purpose of this study was to analyze the effect of using M-learning (mobile motion) on students’ understanding toward Motion System subject matter on XI Science Class. This study uses the Research and Development (RnD) design and the the technique used is a one shoot case study. The research was conducted at SMAN I Sendang Agung with 57 students as the research subject whom divided into 2 classes. The results of the study are as follows: (1) on the subject scoring by subject experts 84, 45% was obtained and 85.33% with very good criteria, and the scoring by media experts 85.49% was obtained and 89.91% with very good criteria so that the media confirmed valid. The score which obtained from students who have used M-Learning Application and then answer the understanding concept questions were obtained an average score 95.7 after being analyzed based on the predetermined Minimum Completeness Criteria (KKM). The specified KKM value is 80. The result show that 94.73% students passed with the very high category. Therefore, it can be state that the use of m-learning (mobile motion) is effective on students understanding concepts.